Kuskokwim Reconnaissance expedition member wading in slough on the Skwentna River, Alaska, July or August 1914 - University of Washington Libraries. Special Collections Division.
Caption under photo: Sloughs of the Skwentna River. McPherson number: K123 PH Coll 495.1-31b Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.